The Impact of Selected Pilates Exercises on the Quality of Life of the Elderly - Babaei chenar, Yahya; Seghatoleslami, Ali; Yousefi, Mohammad (International Journal of Sport Studies for Health, 2024)
Objective: This study aimed to evaluate the impact of selected Pilates exercises on the quality of life among elderly residents of Kalat Naderi, focusing on improvements in physical functioning, mental health, and general well-being.Methods and Materials: A randomized controlled trial design was employed, with 60 participants aged 55 and above, randomly assigned to either an intervention group that participated in a structured Pilates exercise program or a control group that received no intervention. Quality of life was measured at baseline, immediately post-intervention, and at a 3-month follow-up using the SF-36 Health Survey. Data analysis involved ANOVA with repeated measurements and Bonferroni post-hoc tests, conducted using SPSS version 27.Results: The intervention group demonstrated a significant improvement in quality of life scores from baseline (Mean = 54.67, SD = 5.34) to post-test (Mean = 55.23, SD = 4.89), and these gains were maintained at the 3-month follow-up (Mean = 56.12, SD = 4.56). In contrast, the control group showed minimal changes over the same periods. ANOVA results indicated a significant difference between the groups (F = 23.45, p < 0.001), and Bonferroni post-hoc analysis confirmed the significance of improvements in the intervention group compared to the control.Conclusion: The Pilates exercise program significantly enhanced the quality of life for the elderly participants in this study, suggesting that Pilates is an effective intervention for improving physical and mental well-being in this population. These findings indicate the necessity and importance of incorporating structured physical activity, such as Pilates, into the lifestyles of the elderly to promote better health outcomes and quality of life.